2001
DOI: 10.1152/ajpheart.2001.280.6.h2462
|View full text |Cite
|
Sign up to set email alerts
|

EDHF mediates flow-induced dilation in skeletal muscle arterioles of female eNOS-KO mice

Abstract: Vasodilation to increases in flow was studied in isolated gracilis muscle arterioles of female endothelial nitric oxide synthase (eNOS)-knockout (KO) and female wild-type (WT) mice. Dilation to flow (0-10 microl/min) was similar in the two groups, yet calculated wall shear stress was significantly greater in arterioles of eNOS-KO than in arterioles of WT mice. Indomethacin, which inhibited flow-induced dilation in vessels of WT mice by approximately 40%, did not affect the responses of eNOS-KO mice, whereas mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 35 publications
10
118
2
1
Order By: Relevance
“…Studies in which nitric oxide has been blocked pharmacologically or by genetic knockout of eNOS have shown a general compensation for the loss of nitric oxide by upregulation of EDHF or prostacyclin (4,6,16,27). General compensation by combined non-nitric oxide mechanisms is not indicated in the present study, because there is no difference in dilation between control and HHcy arteries with L-NAME (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Studies in which nitric oxide has been blocked pharmacologically or by genetic knockout of eNOS have shown a general compensation for the loss of nitric oxide by upregulation of EDHF or prostacyclin (4,6,16,27). General compensation by combined non-nitric oxide mechanisms is not indicated in the present study, because there is no difference in dilation between control and HHcy arteries with L-NAME (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…We reported previously (13,32) that the mechanisms by which endothelial cells release NO in response to changes in shear stress, elicited by changes in perfusate flow, are altered in certain disease states, such as hypertension and heart failure, as indicated specifically by an impaired flow-induced dilation due to a loss of the NOmediated portion of the responses. However, we also found that in skeletal muscle arterioles of transgenic mice in which the gene for eNOS was deleted, endothelial responses to flow/shear stress are preserved via NO-independent signal transduction pathways, resulting in the release of prostaglandins (31) and EDHF (9), to maintain flow-induced dilations in male and female mice, respectively. Although the capacity of coronary vessels to compensate for the loss of NO-mediated dilations to agonists has already been reported (2,7,18), there are no studies extant that have examined the mechanisms by which coronary arteries are responding to shear stress when the gene for eNOS is deleted.…”
mentioning
confidence: 68%
“…Changes in diameter of coronary arteries in response to increases in perfusate flow were studied (9,31). The vessels were equilibrated at 60 mmHg of perfusion pressure for ϳ1 h in a no-flow condition to develop spontaneous tone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…78,137 EDHF also assumes the same role in endothelial NO synthase (eNOS) knock-out mice, mediating flow-induced vasodilation of arterioles in SMT. 138 Lastly, it is of interest that kinins have Table 1 Contribution of the disrupted skeletal muscle ACE to the etiology of type 2 diabetes, hypertension and atherosclerosis Key: ACE = angiotensin-converting-enzyme; ADH = antidiuretic hormone; Na+ = NESNS = neuroendocrine sympathetic nervous system; SMC = smooth muscle cell. …”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C T mentioning
confidence: 99%